THE EFFECTIVENESS OF SOCIAL MEDIA USE IN EDUCATION IN MAKASSAR CITY SOUTH SULAWESI PROVINCE - Irwandi, Irwandi (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2024)
The purpose of this study was to determine the effectiveness of the use of media technology in this study is the level of education in the province of South Sulawesi Makassar City. Data collection in the form of searching, reading, understanding, selecting data sources, and making relevant and valid literature reviews. The results showed that the use of social media in education in Makassar City, South Sulawesi Province is very effective and has a positive impact. But simultaneously a negative impact also exists on student education. The data obtained based on the results of the analysis in accordance with the topic in general is always growing and increasing rapidly, so monitoring of developments is very necessary and it can be concluded that using the media is very beneficial in the learning process, especially for education.